Implication of total replacement of fish oil with vegetable oils on nutritional and lipid profiles of fish - Christian Larbi Ayisi (Universitas Muhammadiyah Malang, 2021)
In this study, the effects of using vegetable oils solely in finfish feed on nutritional status as well as lipid damage were evaluated. Polyene index (PI), atherogenic index (AI) as well as hypocholesterolemic and hypercholesterolemic fatty acids were assessed. Also, n-3/n-6 and n-6/n-3 ratios were assessed. In all, 32 articles were used for this study after carefully assessing them. Eighteen (18) articles had studied Freshwater species (FWF) whiles fourteen (14) had studied Marine species (MF). TI, n-3/n-6, and n-6/n-3 were significantly higher in fish-fed saturated fatty acids (SFA), n-3, and n-6 dominant vegetables. We document that using vegetable oils without supplementing fish diets with fish oil does not compromise the nutritional status as well as lipid damage. This work provides important information about the effect of using 100% vegetable oils in fish with respect to the nutritional composition of the final product.